Separated Calibration of a Camera and a Laser Rangefinder for Robotic Heterogeneous Sensors. (25th October 2013) - Yu, Lingli; Peng, Meng; You, Zuo; Guo, Ziqi; Tan, Ping; Zhou, Kaijun
The fusion of the heterogeneous sensors can greatly improve the environmental perception ability of mobile robots. And that the primary difficulty of heterogeneous sensors fusion is the calibration of depth scan information and plane image information for a laser rangefinder and a camera. Firstly, a coordinate transformation method from a laser rangefinder coordinates system to an optical image plane is given, and then the calibration of the camera's intrinsic parameters is achieved by "Camera Calibration Toolbox'. Secondly, the intrinsic and extrinsic parameters are separated for calibration are proposed and compared, in which the characteristic parameters' identification is according to some characteristic points on the intersection line. Then Gaussian elimination is utilized for the initial value. Furthermore, the parameters' optimization using the non-linear least square and non-linear Gauss-Newton methods is devised for different constraints. Finally, the simulated and real experimental results demonstrate the reliability and effectiveness of extrinsic and intrinsic parameters' separated calibration, meanwhile, the real-time analysis is achieved for robotic multi-sensor fusion.